Pengaruh Pendapatan Murabahah, Mudharabah, Dan Musyarakah Terhadap Return On Equity (ROE) - Imam Fadilah; Nana Diana (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study uses a quantitative approach with secondary data in the form of the monthly financial reports of PT. BCA Syariah in 2020-2022, to know the effect of murabaha, mudharaba and musyaraka income on return on equity (ROE). The sample of this study used a sampling technique, where all populations aged 35 months were used as samples. This study uses multiple linear regression analysis techniques using IBM SPSS 25. The results of this study reveal that murabaha income has a positive effect on return on equity, mudharaba income has no effect on return on equity, and musyaraka income has a negative effect on return on equity.